Distribution of Polychlorinated-dibenzo-p-dioxins/-dibenzofurans in Soil from Changsha-Zhuzhou-Xiangtan Urban Agglomeration, China - Yue, Jianhua; Peng, Xiaochun; Wu, Yanyu; Hu, Xiaoying (Asian Journal of Chemistry, 2012)
The concentration levels and distribution patterns of polychlorinated-dibenzo-p-dioxins and -dibenzofurans (PCDD/PCDFs) in soil/sediment sampled from Changsha-Zhuzhou-Xiangtan urban agglomeration were preliminarily investigated. The results showed that the concentrations of PCDD/PCDFs in surface soil samples ranged from 267 to 7509 pg/g with 2175.00 pg/g mean concentration. The I-TEQ concentrations were ranged from 0.92 to 10.21 pg/g with mean 4.82 pg/g concentration. The level of PCDD/PCDFs concentration were higher compared with other area of China. The concentrations of PCDD/PCDFs in sediment samples were ranged from 876.17 to 497759.30 pg/g with 160765.91 pg/g mean concentration and the I-TEQ concentrations were ranged from 2.63 to 1031.21 pg/g with mean 332.55 pg/g concentration. The observation that the toxic equivalent concentrations in 50% of sediment samples were over 80 pg/g, indicated that there had posed a threat to some species. Moreover, the distributions of toxic equivalent concentration of 17 single isomers of PCDD/PCDFs in samples were analyzed and the potential pollution sources were discussed. Further researches should be done to get more information about the sources and the distributions of the PCDD/PCDFs.